Clinical Outcomes of Salvage Endoscopic Nasopharyngectomy for Patients With Advanced Recurrent Nasopharyngeal Carcinoma - Li, Wanpeng; Zhang, Huankang; Lu, Hanyu; Wang, Huan; Gu, Yurong; Li, Houyong; Sun, Xicai; Yu, Hongmeng; Wang, Dehui (Frontiers in Oncology, 2021)
Background Salvage endoscopic nasopharyngectomy has better survival prognosis and fewer complications in the management of early stage rNPC, compared to re-irradiation. However, the treatment modality of advanced recurrent nasopharyngeal carcinoma (rNPC) remains controversial. Thus, the purpose of this study was to investigate the demographics, clinical outcomes, and prognostic factors associated with salvage endoscopic nasopharyngectomy in advanced rNPC. Methods This study conducted a retrospective analysis of advanced rNPC patients who underwent salvage surgery betweenm January 2014 and December 2019. The overall survival (OS) and progression-free survival (PFS) were analyzed. Univariable and multivariable analyses of OS and PFS were performed using the Cox regression model. The predicted values of the parameters were determined by means of the receiver operating characteristic (ROC) curve analysis. Results Among the 120 patients included, there were 75 patients with rT3 stage and 45 patients with rT4 stage. With the median follow-up time of 18 months,the 3 -year OS and PFS were 55.2% and 29.4%, respectively. Multivariate analyses showed that the rNPC patients with older age, low BMI (Body Mass Index), rT4 stage, tumor necrosis, and tumor invasion into the ICA was predictive of worse OS, whereas low BMI and rT4 stage were associated with worse PFS. In addition, the rT stage was identified as a better predictor of OS (area under the ROC curve: 0.669; P=0.003) than the other clinical features. Conclusions Salvage treatment using endoscopic nasopharyngectomy appears to be an effective treatment in the management of patients with advanced rNPC. In addition, case matching studies and prospective studies with larger clinical samples are required to further evaluate the efficacy of endoscopic surgery compared with re-irradiation in advanced rNPC.